Penggunaan Metode Drill untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Geografi - Yasir, Muhammad (SCAD Independent, 2024)
This study aims to determine the effectiveness of the drill method in improving student learning outcomes. This Classroom Action Research (CAR) took 35 students of class XII IPS.1 at SMA Negeri 1 Seruway as subjects, consisting of 16 male and 19 female students. Data collection used observation sheets, documentation, pre-test, post-test, and evaluation question sheets. The data analysis stage was carried out by collecting the data that had been obtained and then analyzing it with general theories and concepts related to the facts to correct or investigate the problem. The research activities included planning, action, observation, and reflection. The results of this study indicate that the application of the drill method with a varied and non-monotonous exercise model in learning to practice basic map and mapping skills, student learning outcomes have improved. This is seen in the acquisition of test and evaluation scores in the first cycle increased from 40% to 71% and in the second cycle reached 97.14%. From this increase, it can be said that the application of the drill method is very effective in improving students' geography learning outcomes.